The Role Of Local Enterpreneurship In Reducing The Rate Of Unemployment In Kaligelang Village, Taman District, Pemalang District - lulu maulida (Universitas Islam Negeri (UIN) Salatiga, 2024)
The issue brought up by this study is the contribution of regional business owners to the decline in unemployment. The regional economy frequently suffers from unemployment since it lowers regional output and income, which can lead to poverty and other social issues. Three categories of unemployment have been identified by economists: cyclical, structural, and frictional unemployment. In addition, there are three types of unemployment that are unique to developing nations: underemployment, seasonal unemployment, and hidden unemployment, which is defined as unemployment in which a worker works far less hours than usual. An additional reflection of the unequal distribution of income in society is unemployment. Economic growth capable of reflecting true prosperity can only be achieved through economic equality with fairness and equitable income distribution at all societal levels. The purpose of this study is to explain how local/village entrepreneurs in Kaligelang village, Taman sub-district, Pemalang district, have contributed to a decrease in the unemployment rate. This study takes a descriptive approach while utilizing a qualitative strategy. Data was gathered in Kaligelang village through observation, interviews with local business owners, and a review of the literature. A literature study, also known as library research, gathers data by aggregating information from many literary works. According to the study's findings, local business owners in the craft and culinary industries, like those in Kaligelang village, Taman subdistrict, Pemalang district, can lower the unemployment rate. The study's findings lead to the conclusion that local business owners are crucial in bringing down the unemployment rate in Kaligelang village, Taman sub-district, Pemalang district, making the area a model for other areas trying to combat unemployment.